Pengamanan Protokol MAVLink menggunakan Algoritme Kriptografi Grain-128 - Adam Syahputra; Ari Kusyanti; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Micro Air Vehicle Link or commonly called MAVLink is a communication protocol for UAVs. A document, namely ISO 12100 and ISO 13849 summarized by (Allouch, et al., 2019) states that the MAVLink protocol is a UAV communication protocol that is vulnerable to attacks. The MAVLink protocol vulnerability is known because it does not have a security system support from the confidentiality aspect. To reduce this security risk, it is necessary to make efforts to secure the MAVLink protocol using cryptographic methods to ensure the security of the aspects mentioned above. In this study the Grain-128 cryptographic algorithm was chosen because of its ability to work on low-power devices. In addition to the implementation of the Grain-128 cryptographic algorithm, a security strategy is also implemented, one of which is the IV update system. The purpose of implementing the Grain-128 algorithm and its security strategy is to provide adequate protection for data on the MAVLink protocol. Thus the MAVLink protocol that has been implemented by the security system is resistant to passive attacks and even active attacks.